2019
DOI: 10.1103/physrevb.100.165122
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuations and magnetoresistance oscillations near the half-filled Landau level

Abstract: We study theoretically the magnetoresistance oscillations near a half-filled lowest Landau level (ν = 1/2) that result from the presence of a periodic one-dimensional electrostatic potential. We use the Dirac composite fermion theory of Son [Phys. Rev. X 5 031027 (2015)], where the ν = 1/2 state is described by a (2+1)-dimensional theory of quantum electrodynamics. We extend previous work that studied these oscillations in the mean-field limit by considering the effects of gauge field fluctuations within a lar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 77 publications
(128 reference statements)
0
17
0
Order By: Relevance
“…These are puzzling at first sight, and might imply a breakdown of particle-hole symmetry. The question of whether or not the CFs obey the particle-hole symmetry has in fact sparked exciting new developments in the field of strongly interacting electron systems [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]40]. These theories mostly predict that the particle-hole symmetry should hold within the lowest LL, while Balram et al, [20] conclude that it could be broken when LLM is significant.…”
mentioning
confidence: 99%
“…These are puzzling at first sight, and might imply a breakdown of particle-hole symmetry. The question of whether or not the CFs obey the particle-hole symmetry has in fact sparked exciting new developments in the field of strongly interacting electron systems [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]40]. These theories mostly predict that the particle-hole symmetry should hold within the lowest LL, while Balram et al, [20] conclude that it could be broken when LLM is significant.…”
mentioning
confidence: 99%
“…19 They found that (27) fit their data points better than the simple formula E g = C/|∆B|, though both formulas contain a single fitting parameter. However, it is impossible to draw firm conclusions from such small systems, and the data would also be compatible with an asymptotic dependence of the form (29).…”
Section: Infrared Divergencesmentioning
confidence: 91%
“…Recent work by Mitra and Mulligan has suggested that the discrepancy may be an effect of gauge fluctuations. 29 Minima in the magneto-exciton spectrum and maxima in the static structure factor.…”
Section: Weiss Oscillationsmentioning
confidence: 99%
“…Figure 1(c) zooms in around ν = 1/4. From the period of the modulation, a = 240 nm, we determine the expected positions for the primary i = 1 GR resistance minima according to [3,10,15,16,21,22,26,27]. The difference between the expected B i=1 for the two assumptions is very small and cannot be resolved in our experiments.…”
mentioning
confidence: 97%
“…For example, recent GR measurements of 2 CF Fermi sea revealed an unexpected asymmetry between the two sides of ν = 1/2 [9]. This asymmetry, and more generally the question of particle-hole symmetry, inspired renewed interest in the physics of a half-filled LL [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Notable among the new studies is the theory involving a Dirac fermion description [10,[15][16][17][18][19][21][22][23][24][25][26][27].…”
mentioning
confidence: 99%